SISTEM DEDUKTIF AKSIOMATIS DALAM MATEMATIKA DAN MATEMATIKA SEKOLAH - Amin Suyitno (Universitas PGRI Semarang, 2010)
In school mathematics, words definition, axiom, or theorem tend to be avoided. Expert of mathematics education (in Indonesia) seem to have fear, so that the words definition, axiom, or theorem are taboo to appear in a Mathematics Textbook for students.?é?á Seem to worry if the words such as definition, axiom, or theorem that appear in math textbooks, then students in Indonesia is estimated to be scared and stay away from mathematics. Really? Are not definitions, axioms, or theorems are the strong pillars supporting the beautiful buildings of Mathematical structure, able to distinguish it from other sciences? Mathematics has the characteristics: (1) abstract objects, (2) based-on agreements, (3) fully using deductive thinking, and (4) consistent, which is preceded by the previous truths. If consistent with the characteristics of this mathematics, the school mathematics should also reflect these characteristics. Key words :?é?á axoims, define